GAMBARAN POLA ASUH DAN STATUS GIZI BALITA PADA IBU YANG MENIKAH DIUSIA DINI DI DESA SEBERAYA KECAMATAN TIGA PANAH KABUPATEN KARO PROVINSI SUMATERA UTARA TAHUN 2017 - Elisa Efelinda siregar; Albiner Siagian; Fitri Ardiani (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2017)
One of the causes of nutritional problems or Children's growth and development is nurturing,. Among others, gives attention, time and support for comply the physical, mental, and social children. Mothers who get married at an early age may not yet understand the good parenting, especially in the fulfillment of nutrition. The purpose of this study is to know the description of parenting with the nutritional status of children in mothers who were married at an early age in the village Tiga Panah Seberaya Karo district of North Sumatra province Year 2016. This type of research is descriptive research with cross sectional design. The population is all toddlers which born from mothers who married under the age of 19 years, amounting to 66 (total sampling). The data collected in this study include eating pattern, cleanliness pattern, health care pattern and nutrition status of a toddler based on W/A, H/A and W/H. The method used is a direct interview using a questionnaire to know the action of mothers in giving the pattern of eating, pattern of hygiene, and health pattern for toddlers. Then, to obtain data on weight and height toddlers do for weighing and measuring. The data obtained were analyzed using Chi-square test. The results showed that category of good eating pattern is 50%, and category of not good eating pattern is 50%, the category of good cleanliness pattern is 51.5%, and the lowest category of not good cleanliness pattern is 48.5%, and category of health care pattern is 75.8% and the lowest category of not good health care pattern is 24.2%. While the nutritional status of children is based on W/A mostly in the category of malnutrition is 63.6% and the lowest category of good nutrition is 36.4%, nutritional status of children based on H/A mostly in the normal category is 65.2% and the lowest category short is 34.8%, and the nutritional status of children is based on W/H mostly in skinny category is 69.7% and the lowest normal category is 30.3%. Toward health workers to improve the activities about good parenting to the mother and invites mothers to do regularly weigh and height measurement to monitor the abnormal growth of underfive children. Keywords : Parenting, Underfive Children, Nutritional Status, Early Marriage